The Effect of the Problem Based Learning (PBL) Learning Model Assisted by CANVA Media on Elementary School Students' Learning Motivation and Learning Outcomes - Noorma Lenny; Banun Havifah Cahyo Khosiyono; Syarifuddin Syarifuddin (Journal of General Education and Humanities, 2026)
This study aims to examine the relationship between the Problem Based Learning (PBL) model assisted by Canva media and elementary school students’ learning motivation and learning outcomes. The research employed a quantitative approach supported by qualitative data obtained through teacher interviews. Quantitative data were analyzed using the Wilcoxon test on students’ learning motivation scores as well as pretest and posttest results. The findings indicate that the implementation of the PBL model assisted by Canva media has a significant relationship with the improvement of students’ learning motivation, as reflected in increased interest, activeness, confidence in expressing opinions, and seriousness in participating in learning activities. In addition, students’ learning outcomes also showed a significant improvement, not only in written test scores but also in their ability to understand the material, answer questions, and verbally express their understanding during the learning process. Simultaneously, increased learning motivation positively contributes to improved learning outcomes. Therefore, it can be concluded that the PBL model assisted by Canva media is effective in creating a more engaging, meaningful, and effective learning process, particularly in Indonesian language subjects at the elementary school level.